2019
DOI: 10.1186/s42523-019-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis on broiler-associated Clostridium perfringens strains and exploratory caecal microbiome investigation reveals key factors linked to poultry necrotic enteritis

Abstract: Background: Clostridium perfringens is a key pathogen in poultry-associated necrotic enteritis (NE). To date there are limited Whole Genome Sequencing based studies describing broiler-associated C. perfringens in healthy and diseased birds. Moreover, changes in the caecal microbiome during NE is currently not well characterised. Thus, the aim of this present study was to investigate C. perfringens virulence factors linked to health and diseased chickens, including identifying putative caecal microbiota signatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…Genomic DNA extraction of mouse caecal samples on day 4 was performed with FastDNA Spin Kit for Soil following manufacturer’s instructions and extending the bead-beating step to 3 min as described previously [56]. Extracted DNA was quantified, normalised and sequenced on Illumina MiSeq platform using a read length of 2 × 300 bp, sequencing reads were analysed using OTU clustering methods (QIIME v1.9.1) to assign bacterial taxonomy and visualised as described previously [57, 58]. PCA was performed via R package ggfotify function autoplot and prcomp , while diversity index was computed via package vegan [59-61].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA extraction of mouse caecal samples on day 4 was performed with FastDNA Spin Kit for Soil following manufacturer’s instructions and extending the bead-beating step to 3 min as described previously [56]. Extracted DNA was quantified, normalised and sequenced on Illumina MiSeq platform using a read length of 2 × 300 bp, sequencing reads were analysed using OTU clustering methods (QIIME v1.9.1) to assign bacterial taxonomy and visualised as described previously [57, 58]. PCA was performed via R package ggfotify function autoplot and prcomp , while diversity index was computed via package vegan [59-61].…”
Section: Methodsmentioning
confidence: 99%
“…The major site of Clostridium perfringens- host interactions in chickens is the gastrointestinal tract (GIT). Thus, this environment is an important anatomical region in which to investigate mechanisms involved in the response to Clostridium perfringens challenge and for the development of agents that may potentially regulate this response [ 12 ]. Identifying the mechanisms by which NE can be limited may provide new insights into biosecurity.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, they were detected in 26% and 22% of isolates of environmental origin (soils, water, and sewage) [8]. The proportion of isolates carrying the erm(Q) gene (13.6%) in the digestates of the two BGPs fed with pig manure was also higher than that previously observed in isolates that were collected from broiler chickens (4.5%) and in environmental samples (1%) [8,14].…”
Section: Tetracycline and Erythromycin Resistance Genes Of C Perfrinmentioning
confidence: 75%
“…Their prevalence in digestates was slightly higher than that reported in other matrices. Indeed, Kiu et al [14] observed a frequency of detection of tetA(P) alone and of the tetA(P)-tetB(P) gene of 14.8% and 35.2% in isolates from broiler chickens, respectively. In another study, they were detected in 26% and 22% of isolates of environmental origin (soils, water, and sewage) [8].…”
Section: Tetracycline and Erythromycin Resistance Genes Of C Perfrinmentioning
confidence: 99%
See 1 more Smart Citation